Russian Cities in Transition : The Impact of Market Forces in the 1990s - Ira N. Gang; Robert C. Stuart (Rutgers University, Department of Economics, 2004)
This paper analyses Russian city growth during the command and transition eras. Our main focus is on understanding the extent to which market forces are replacing command forces, and the resulting changes in Russian city growth patterns. We examine net migration rates for a sample of 171 medium and large cities for the period 1960 through 2002. We conclude that while the declining net migration rate was reversed during the first half of the 1990s, restrictions continued to matter during the early years of transition in the sense that net migration rates were lower in the restricted than in the unrestricted cities. This pattern seemingly came to an end in the late 1990s.
Keywords: R23; J6; P20; 330; cities; city growth; migration; Russia; urbanization; Stadtwachstum; Binnenwanderung; Urbanisierung; Übergangswirtschaft; Russland